x = 4, y = 1
Step 1: use the equations given to find an equation with only 1 term. Here I used x.
(x + 2y) + (x - 2y) = 2x = 6 + 2 = 8
2x = 8
x = 4
Step 2: substitute x = 4 into either given equation. Here I used the first equation x + 2y = 6.
(4 + 2y) = 6
2y = 6 - 4 = 2
y = 1
This solution can also be done by finding y in step 1 or using the other given equation in step 2.
Hope this helped!
Answer:
your answer would be -18
Step-by-step explanation:
kcf, -55 + 37 = 18 or -55 - (-37) = -18
Answer:
9
Step-by-step explanation:
if scale factor is 3/5, then
(x+12):35=3:5, ⇒
L = 0 bcause it cancels itself out